SERANGAN MALWARE RANSOMWARE DALAM PERSPEKTIF TRANSNATIONAL CRIME - Batu, Dewi Pika Lbn; Siahaan, Parlaungan Gabriel; Ramadhan, Taufiq; Silitonga, Agnes Irene (Gapenas Publisher, 2025)
Nowadays, malware attacks are a national and global concern. Malware is software designed to harm or disrupt computers in some way including viruses, worms, Trojans, backdoors, ransomware and other malicious programs. Malware spreads and infects computer systems in various ways. In this research, the author focuses on studying ransomware. Ransomware is a form of malware that infiltrates computer devices to block access to information, basically blocking files and demanding ransom to give access back to the information. Hackers use the double extortion method, encrypting and stealing data with the threat of being published to the media if the ransom is not paid immediately. In recent years, ransomware attacks have occurred in Indonesia, such as the wannacry ransomware attack on Harapan Kita Hospital and Dharmais Hospital, the lockbit ransomware attack on Bank Syariah Indonesia and the ramsonware brain cipher attack on the National Data Center. Moreover, cybercrime is a transnational crime, which can be committed across national borders, so in this case regulation is also a major challenge in handling cybercrime cases.